Graphene nanosheets produced via controlled detonation of hydrocarbons - Nepal, Arjun (Kansas State University, 2015)
We demonstrated that gram quantities of pristine graphene nanosheets (GNs) can be produced via detonation of a hydrocarbon. This one-step and catalyst-free method is eco-friendly and economical for the production of GNs. The hydrocarbons detonated were C₂H₂, C₂H₄, C₃H₈ and CH₄ in the presence of O₂. The carbon products obtained from the detonation were analyzed by XRD, TEM, XPS and Raman spectroscopy. Depending upon the ratio of O₂ to C₂H₂, the GNs of size up to ~ 250 nm, SSA up to ~ 200 m²/g and yield up to 70% with 2-3 layers' stack have been obtained so far. N₂O was determined as a good alternative to O₂ as an oxidizer to produce GNs by detonating C₂H₂ with it. A two-color pyrometer was designed and calibrated to measure the temperature of the detonation of hydrocarbons. The measured detonation temperatures were in between 2700 K and 4300 K. Along with the high detonation temperature, the composition of precursor hydrocarbon was observed to be crucial as well to determine its suitability to detonate with oxidizer to produce GNs. The hydrocarbons C₂H₂ and C₂H₄ were determined as the suitable precursors to produce GNs whereas detonation of C₃H₈ yields mere amorphous carbon soot and CH₄ gives no solid carbon while detonated with O₂. It has been proposed that the hydrocarbons with C/H≥0.5 are suitable for GNs production by detonation method. Highly oxidized graphene nanosheets (OGNs) were produced by solution-based oxidation of GNs prepared via a controlled detonation of acetylene at O₂/C₂H₂=0.8. The produced OGNs were about 250 nm in size and hydrophilic in nature. The C/O ratio was dramatically reduced from 49:1 in the pristine GNs to about 1:1 in OGNs, as determined by X-ray photoelectron spectroscopy. This C/O in OGNs is the least ever found in all oxidized graphitic materials that have been reported. Thus, the OGNs produced from the detonated GNs with such high degree of oxidation herein yields a novel and promising material for future applications.
Keywords: Hydrocarbons detonation; Graphene Nanosheets; Pyrometer; Materials Science (0794); Physics (0605)